Development of A Diagnostic Test in The Form of A Three Tier Essay Test to Identify Understanding of Mathematical Concepts on The Material of The System of Linear Equations of Three Variables - Azma, Nur; Mania, Sitti; Baharuddin (Department of Mathematics Education, 2024)
This study aims to develop and produce a three tier essay test instrument to identify understanding of mathematical concepts on the material of the system of linear equations of three variables (SPLTV). This research is categorized as development research with the Formative Research development model (Tessmer) through the stages of (1) preliminary, (2) self evaluation, (3) prototyping, and (4) field test. The test subjects in this study were students of class X.2 MAN 1 Soppeng. This development research produces (1) a diagnostic test instrument in the form of a three tier essay test which is used to identify students' understanding of mathematical concepts on SPLTV material; (2) the three tier essay test developed meets the valid criteria because the average score on the CVR and CVI is 1 with a very suitable category, the average results of the one to one stage student response questionnaire trial of 77.78% with a positive category and at the small group stage of 85.19% with a very positive response category, the average result of the analysis of the difficulty level of the question is 0, 54 with a moderate category, the average result of the differentiator analysis of 0.33 with a sufficient category, and the reliability test result of 0.963 with a very high interpretation (reliable), and the results of data analysis of the results of the three tier essay test at the field test stage obtained the average ability to understand the mathematical concepts of class X students. 2 MAN 1 Soppeng in Tier I, which is 46.45%, is in the sufficient category. The results of categorizing the ability to understand the mathematical concepts of students obtained as many as 23.27% have scientific knowledge, 19.81% have misconceptions, 0% have no confidence, and as many as 56.92% lack understanding; (3) students experience errors in understanding the concept of SPLTV material, transformation errors, errors in understanding the problem, and errors in the calculation process. This is because students are less careful in reading and understanding the meaning of the problems they do.